The Green Supply Chain and Its Role in Enhancing Organizational Performance: an Analytical Study of The Opinions of a Sample of Employees at Doha Cement Plant - Ahmed Arrak Abed; Ali Saud Bisheen (Research Parks Publishers, 2026)
The current research aims to identify the role of the green supply chain in achieving outstanding performance at Doha Cement Plant. Based on the above, the research adopts a descriptive and analytical approach to the research variables. The research sample consisted of a group of (188) employees at Doha Cement Plant. A questionnaire was used as the primary tool for data collection. The research employed several statistical methods, such as standard deviations, arithmetic means, and structural equation modeling with the help of statistical programs (SPSS.var.29, AMOS.var.26). The current research reached a set of conclusions, the most important of which is that the green supply chain has a significant impact on outstanding performance.